2011
DOI: 10.1159/000328762
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Bone Marrow Cells by CSF3 Protects Mice from Bleomycin-Induced Lung Injury

Abstract: Background: Bone marrow-derived cells may play a role in tissue injury and repair. Growth factors facilitate the mobilization of bone marrow-derived cells to the site of injury. Objectives: The aim of this study was to determine the effect of the mobilization of autologous bone marrow-derived cells by granulocyte colony-stimulating factor (CSF3) on bleomycin-induced lung injury in mice. Methods: The bone marrow from male green fluorescent protein transgenic (C57Bl/6J) mice was transplanted into irradiated fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Cell culture data have suggested that the loss of the defining differentiation potential of MSCs occurs in a hierarchical manner, whereby the ability for adipogenic differentiation is commonly abolished first prior to the loss of the chondrogenic differentiation potential, finally giving rise to osteogenic precursor cells4243. The observed reduction in the differentiation potential of MSCs may bear therapeutic significance, as previous publications have reported regenerative effects of mobilized endogenous MSCs in bleomycin-induced pulmonary fibrosis4445. In these datasets, pulmonary damage was mostly induced by topical intratracheal instillation of bleomycin, thereby preserving MSCs of other tissues46.…”
Section: Discussionmentioning
confidence: 96%
“…Cell culture data have suggested that the loss of the defining differentiation potential of MSCs occurs in a hierarchical manner, whereby the ability for adipogenic differentiation is commonly abolished first prior to the loss of the chondrogenic differentiation potential, finally giving rise to osteogenic precursor cells4243. The observed reduction in the differentiation potential of MSCs may bear therapeutic significance, as previous publications have reported regenerative effects of mobilized endogenous MSCs in bleomycin-induced pulmonary fibrosis4445. In these datasets, pulmonary damage was mostly induced by topical intratracheal instillation of bleomycin, thereby preserving MSCs of other tissues46.…”
Section: Discussionmentioning
confidence: 96%
“…Pulmonary damage occurring in up to 20% of patients is commonly the dose‐limiting toxicity of bleomycin . Preclinical datasets have suggested an attenuation of bleomycin‐induced lung fibrosis by treatment with allogeneic MSCs or activated endogenous MSCs . However, considering the sensitivity and impaired differentiation potential of these stem cells, further analyses are needed investigating the impairment of the MSCs' regenerative abilities by bleomycin treatment.…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%
“…G-CSF is a hematopoietic mobilizer and has been applied to all types of leucopenia in the clinical setting. It has been shown that G-CSF can accelerate the regression of fibrosis in organs including heart, lung and liver [4] [7] . However, whether it has the anti-fibrotic effects in pancreas is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, BM cells migrate into the diseased organ and further differentiate into myofibroblasts. These BM-derived myofibroblasts has been showed to participate in fibrosis in organs including heart, lung, liver and kidney [4] [7] . Conversely, there is a growing body of evidence that the BM-derived cells may contribute to the regression of fibrosis [8] .…”
Section: Introductionmentioning
confidence: 99%